Public health : innovation and intellectual property rights : report (WHO GenevaCH, 2006)
Analyzes intellectual property, innovation and public health including the question of appropriate funding and incentive mechanisms for the creation of new medicines and other products against diseases that disproportionately affect developing countires.
Keywords: INTELLECTUAL PROPERTY